Dinosaur's day - Thomson, Ruth, 1949- (London : Dorling Kindersley, 2009)
A gentle Triceratops forgets to stay with the herd and has to use his sharp horns to fight a Tyrannosaurus.
Originally published: 2000.
Keywords: Dinosaurs -- Juvenile fiction; Readers (Elementary); Children's stories; High interest-low vocabulary books